Influence of the addition of PEG into PCL‐based waterborne polyurethane‐urea dispersions and films properties. Issue 26 (19th December 2019) - Vadillo, Julen; Larraza, Izaskun; Arbelaiz, Aitor; Corcuera, Maria Angeles; Save, Maud; Derail, Christophe; Eceiza, Arantxa
ABSTRACT: In this work, segmented waterborne polyurethane‐urea (WBPUU) dispersions containing hydrophobic polycaprolactone (PCL) and hydrophilic poly(ethylene glycol) (PEG) in different molar ratios are synthesized and used for the subsequent preparation of films by casting. The molar ratio of PEG is gradually increased up to 0.20 in order to analyze the effect of low hydrophilic PEG content (from 1.7 to 7.1 wt %) on the properties of resulting dispersions and films. Regarding the dispersions, the addition of PEG results in an increase of the particle size, from 86 ± 1 in the case of pure PCL‐based system to 112 ± 15 for systems containing 7.1 wt % of PEG, as well as in the formation of a core–shell structure in the particles. Films show different behaviors depending on their PEG content. WBPUUs containing just PCL or very low content of PEG in the soft segment present higher stiffness. However, the addition of PEG in a content of 3.4 wt % or higher hinder the ability of the short‐range ordering of the hard segment, increasing the elongation at break from 842 ± 102 MPa for PCL‐based WBPUU to 1312 ± 84 MPa for the system with the highest PEG content. Systems with higher PEG content form nanoparticles with more segregated core–shell structures inducing to the film a higher hydrophilicity. Hence, the addition of PEG to a PCL‐based WBPUU allows to tune the properties of the resulting film increasing the range of application of these materials. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2020, 137, 48847. Abstract : The incorporation of PEG in the polyurethane soft segment leads to a reinforced core‐shell structure.